PP.20.05: HIGHER NEUTROPHIL TO LYMPHOCYTE RATIO AND HYPERDINAMIC CIRCULATION COULD MEDIATE RISK OF ARTERIAL STIFFNESS IN DEPRESSIVE SUBJECTS. (June 2015) - Obregon, S.; Haehnel, M.; Huguet, E.; Cadenas, M.; Brandani, L.; Koretzky, M.; Manccanelli, G.; Pardini, P.; Dulude, E. Perasso; Sabate, D.; Vigna, L.; Carrizo, P.; et al.
Abstract : Objective: Altered autonomic balance and inflammatory activation have been both suggested as phisiopathologycal mechanisms involved in the association of depression and increased cardiovascular morbidity and mortality.Recent studies have shown a strong predictive value of Neutrophil-Lymphocyte Ratio (NLR) for the risk of coronary heart disease. Higher values of NLR are useful to reclassify arteriosclerotic risk in subjects at low CV risk. On the other hand, high-sensitivity C-Reactive Protein (hsCRP) has been widely linked to cardiovascular inflammation. To evaluate, in subjects with subclinical depression, the hemodynamic mechanisms of blood pressure control and blood sample determinations like neutrophil/lymphocyte ratio (NLR) and hs-CRP, as representative of inflammatory activation. Design and method: We included 240 subjects without history of cardiovascular events in a prospective cohort. After completion of the SCL-90-R (Hopkins Symptom Checklist-HSCL, Derogatis et al, 1977-1994) we consider the depression scale to analysis. Determinations of cardiac index and vascular resistance, and pulse wave velocity (PWV), were obtained by non-invasive measurements (Mobil-O-Graph™). NLR and hs-CRP determinations were obtained in a 12 hour-fasting blood sample. Results: After applying exclusion criteria, we finally included 120 subjects, 57 ± 14.8 years, 50% female, controlled hypertensive 57% (n:68, 131 ± 7.6/ 76 ± 9 mm Hg), normotensive 43% (n: 52). The median score in SCL-90-R was 113.5 ± 15.87 points. Depression was more prevalent in females and in hypertensive individuals. An increased cardiac index was predominant in depressive subjects with higher scores, and a direct continue association was observed between cardiac index and depression (Rho: 0.3044, Spearman, p = 0.02), and between vascular resistance and depression (Rho:-0.2812, Spearman, p = 0.04). Both NLR and hs-CRP showed efficacy to identify individuals with depression and elevated PWV (>10 m/s; p < 0.0001). Conclusions: NLR and hs-CRP showed efficacy to detect atherosclerosis risk in asymptomatic low risk subjects with depression. Inflammatory activation plus hyperdinamic cardiac response could be associated with autonomic misbalance in these condition, known to increase cardiovascular risk in this population.